Probiotic Weissella cibaria LAB_Weis_Camel_L4 mitigates Escherichia coli-induced enteritis via competitive exclusion and microbiota modulation - Jin, Wanjing; Zhang, Mengfei; Lan, Xueqin; Huang, Ying; Bai, Yixin; Li, Yingchao; Shi, Chenyang; Song, Yaolong; Wang, Lei; Zhang, Yi; Zhang, Wei; Aishan, Gulina; et al. (Frontiers in Immunology, 2025)
BackgroundPathogenic Escherichia coli (E. coli), a significant zoonotic pathogen, contributes to considerable economic losses worldwide by causing enteric disease in neonatal animals. The therapeutic efficacy of conventional antibiotics is increasingly undermined by the development of antimicrobial resistance and perturbations in ecological homeostasis. This study introduces a novel probiotic-based intervention, systematically assessing the therapeutic potential of the newly isolated Weissella strain LAB_Weis_Camel_L4 in a mouse model of E. coli-induced enteritis. Furthermore, it investigates the underlying mechanism through which this probiotic modulates intestinal homeostasis, focusing on the “microbiota–gut–immunity” pathway.MethodsIn this study, the Weissella strain LAB_Weis_Camel_L4 was systematically isolated and identified, followed by a comprehensive in vitro evaluation of its probiotic properties, including growth kinetics, acid production, and tolerance to acidic pH and bile salts. Genomic analyses were performed to assess safety at the molecular level. An enteritis mouse model induced by pathogenic E. coli was then established to evaluate the in vivo safety and therapeutic efficacy of LAB_Weis_Camel_L4 through histopathological examination. Furthermore, 16S rRNA sequencing was performed to characterize alterations in gut microbiota composition following probiotic intervention.ResultsA novel Weissella strain, LAB_Weis_Camel_L4, was identified and showed strong probiotic characteristics. In vitro assays revealed high gastrointestinal tolerance (survival rate > 80%) and significant antibacterial activity (inhibition zones ranging from 12.57 to 16.76 mm). Genomic analysis verified its safety, with no detectable antibiotic resistance or virulence-associated genes. In vivo studies demonstrated that LAB_Weis_Camel_L4 significantly decreased mortality in E. coli-infected mice (p < 0.01), mitigated intestinal inflammation, and suppressed pathogenic colonization by modulating gut microbiota composition, highlighting its therapeutic potential.ConclusionsWeissella LAB_Weis_Camel_L4 significantly attenuates E. coli-induced intestinal inflammation and promotes mucosal barrier restoration via dual mechanisms involving microbiota modulation and competitive exclusion. Its potent microecological antagonistic activity and capacity to maintain intestinal homeostasis position it as a strong probiotic candidate for antibiotic substitution.